2015
DOI: 10.1515/bot-2014-0093
|View full text |Cite
|
Sign up to set email alerts
|

Benthic-epiphytic dinoflagellates from the northern portion of the Mesoamerican Reef System

Abstract: In 2010, we surveyed 42 sampling locations at 11 sites along the Mexican part of the Mesoamerican Reef System, including eight protected natural areas of the coastal state of Quintana Roo, to determine the richness of benthic-epiphytic dinoflagellates in the area. At each site, the host macroalgae of the genera Dictyota, Halimeda, Laurencia, Sargassum, and Stypopodium were manually collected. A total of 383 samples were analyzed microscopically using transmitted light, epifluorescence with calcofluor staining,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Once in the laboratory, macroalgae samples were processed following the protocol by Reguera et al (2011) as follows: samples were vigorously shaken (2 min) to detach the cells. Macroalgae were removed, and the water suspension was filtered and washed with filtered seawater (TCLP glass fiber filters, 0.7 µm; Pall Laboratory, Port of Mexico and the Yucatán Peninsula (Okolodkov et al 2007, Almazán-Becerril et al 2015.…”
Section: Collection and Preliminary Handling Of Macroalgae Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…Once in the laboratory, macroalgae samples were processed following the protocol by Reguera et al (2011) as follows: samples were vigorously shaken (2 min) to detach the cells. Macroalgae were removed, and the water suspension was filtered and washed with filtered seawater (TCLP glass fiber filters, 0.7 µm; Pall Laboratory, Port of Mexico and the Yucatán Peninsula (Okolodkov et al 2007, Almazán-Becerril et al 2015.…”
Section: Collection and Preliminary Handling Of Macroalgae Samplesmentioning
confidence: 99%
“…However, the seagrasses Halodule wrightii Ascherson 1868 and Syringodium filiforme Kützing 1860 are also dominant species in the Gulf of Mexico, along with mainly green macroalgal species, such as Caulerpa ashmeadii Harvey 1858, C. paspaloides (Bory) Greville 1030, C. prolifera (Forsskål) J. V. Lamouroux 1809, Halimeda incrassata (J. Ellis) J. V. Lamouroux 1816, and Udotea flabellum (J. Ellis & Solander) M. Howe 1904 (Okolodkov et al 2007). In the Mexican Caribbean, Coolia species have been found associated with Amphiroa J. V. Lamouroux, 1812 and Dictyota, J. V. Lamouroux, 1809; particularly, C. tropicalis is a very conspicuous species on a variety of macroalgae along the coast (Almazán-Becerril et al 2015). In Bahía de La Paz, southern Gulf of California, Coolia malayensis was isolated from Sargassum horridum Setchell & N. L. Gardner 1924(Sepúlveda-Villarraga 2017.…”
Section: Collection and Preliminary Handling Of Macroalgae Samplesmentioning
confidence: 99%
“…Amphidiniella sp. Núñez-Vázquez, 2005;Okolodkov et al, 2007Okolodkov et al, , 2014Okolodkov et al, , 2016Gárate-Lizárraga, 2012, 2020Hernández-Castro, 2017;Aguilar-Trujillo et al, 2014Almazán-Becerril et al, 2015;Martínez-Cruz et al, 2015 Okolodkov & Gárate-Lizárraga, 2006;Okolodkov et al, 2007Okolodkov et al, , 2014Morquecho et al, 2016;Almazán-Becerril et al, 2016b Okolodkov et al, 2007Okolodkov et al, , 2014Okolodkov et al, , 2016Aguilar-Trujillo et al, 2014Almazán-Becerril et al, 2015, 2016bIrola-Sansores et al, 2018;Méndez-Torres, 2019 The first sequence data for genus Amphidinium from Mexico was provided from the study to determine the toxigenicity and cytotoxic effects of A. operculatum in culture (Mejía-Camacho et al, 2021). The identification of Amphidinium strain AA60 as A. operculatum was confirmed by SEM and sequencing of the LSU and ITS regions of rDNA.…”
Section: Referencesmentioning
confidence: 99%
“…The primary focus on a handful of key BHAB species has been necessary because of resource and personnel limitations, but has led to a relative neglect of cryptic, rare and non-BHAB taxa -hence a likely underestimate of diversity of benthic dinoflagellates in Mexican waters. In most cases, taxonomic studies have simply corroborated original descriptions based on morphological traits and strengthened local knowledge for accurate species identification (Cortés-Altamirano & Sierra-Beltrán, 2003;Hernández-Becerril & Almazán-Becerril, 2004;Almazán-Becerril et al, 2015, 2016a. A few more profound taxonomic investigations have indeed contributed to reclassification of genera or species within newly created genera or to resolving species complexes (Tarazona-Janampa et al, 2020;Cembella et al, 2021).…”
Section: Speciesmentioning
confidence: 99%
“…Benthic dinoflagellate species are quite well described morphologically from Latin America (reviewed in Durán-Riveroll et al (2019) but there are many gaps in known phylogeographical distribution, few confirmed records of cell toxicity or toxin composition and a paucity of molecular confirmation of species identities and phylogenetic relationships. This poor state of knowledge also applies to benthic Prorocentrum species although members of the genus have been reported and described from both the Pacific [for references, see Okolodkov and Gárate-Lizárraga (2006); Gárate-Lizárraga et al (2007)], and Gulf of Mexico and Caribbean coasts of Mexico (Okolodkov et al, 2007(Okolodkov et al, , 2014Barón-Campis et al, 2014;Almazán-Becerril et al, 2015;Aguilar-Trujillo et al, 2017).…”
Section: Introductionmentioning
confidence: 99%